Cover Image, Volume 86, Issue 3. Issue 3 (8th February 2018) - Mondal, Manas; Chakrabarti, Jaydeb; Ghosh, Mahua
Abstract : The cover image, by Manas Mondal et al., is based on the Research Article Molecular dynamics simulations on interaction between bacterial proteins: Implication on pathogenic activities, DOI:10.1002/prot.25446 .